2011
DOI: 10.1364/oe.19.003077
|View full text |Cite
|
Sign up to set email alerts
|

Multi-µJ coherent extreme ultraviolet source generated from carbon using the plasma harmonic method

Abstract: We demonstrate intense high-order harmonic generation from plasma that is created from different carbon targets. We obtain high-order harmonic energy in the multi-microjoule range for each harmonic order from the 11th to the 17th harmonic. By analyzing the target morphology and the plasma composition, we conclude that the intense harmonics from the bulk carbon targets originate from nanoparticles target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…In addition, the efficiency of conversion to an individual (resonantly enhanced) high-order harmonic approached 10 À4 [37,38]. Recent studies of carbon plasma have revealed that the high-order harmonics from this medium can also achieve 10 À4 conversion efficiency, thus reaching the microjoule level of pulse energies for these XUV sources [39,40]. The majority of these parameters are at the same level as the results obtained in gas media.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…In addition, the efficiency of conversion to an individual (resonantly enhanced) high-order harmonic approached 10 À4 [37,38]. Recent studies of carbon plasma have revealed that the high-order harmonics from this medium can also achieve 10 À4 conversion efficiency, thus reaching the microjoule level of pulse energies for these XUV sources [39,40]. The majority of these parameters are at the same level as the results obtained in gas media.…”
Section: Introductionmentioning
confidence: 64%
“…Below, the most recent developments and some fresh approaches, experimental schemes and ideas are described, which could considerably push this field toward the dramatic improvement of the output characteristics of harmonics. The intense HHG from plasma that is created from different carbon targets was demonstrated recently in [39]. A high-order harmonic energy in the multimicrojoule range for each harmonic order from the 11th to the 17th harmonic was obtained.…”
Section: New Trends Schemes and Approaches In Plasma Hhgmentioning
confidence: 94%
See 2 more Smart Citations
“…It means that the harmonic generation was carried out during interaction of the laser pulse with small amount of the potential emitters of coherent radiation. Previous studies of plasma harmonics were performed using significantly longer plasma plumes (0.5-5 mm) [13][14][15][16][17][18][19][20]. Further, the short delay between pulses (8 ns) did not allow the whole cloud of ablated particles to propagate the distance equal to the radius of drilled hole (*40 lm).…”
Section: Resultsmentioning
confidence: 99%